Heart Transplantation - Loforte, Antonio; Montalto, Andrea; Amarelli, Cristiano (IntechOpen, 2018)
One of the most challenging scientific steps of the modern era has been the ability to replace, functionally or anatomically, the failing heart, and in December 2017 we celebrated the 50th anniversary of the world's first human heart transplant. Despite a long and troubled hystory, heart transplantation has dramatically expanded over time, and is currently the "gold standard" solution in terms of treatment of refractory end-stage heart failure. Thanks to the contributions by well-known experts in the field, the goal of this book is to provide a framework for successful transplant program development and management. The text reflects the global collective efforts of those who have dedicated countless energy to achieving a better understanding of the details that will ultimately yield better outcomes in terms of teamwork.